2016
DOI: 10.1113/jp271728
|View full text |Cite
|
Sign up to set email alerts
|

Perpetuation of torsade de pointes in heterogeneous hearts: competing foci or re‐entry?

Abstract: Torsade de pointes (TdP) can be the consequence of cardiac remodelling, drug effects or a combination of both. The mechanism underlying TdP is unclear, and may involve triggered focal activity or re-entry. Recent work by our group has indicated that both cases may exist, i.e. TdPs induced in the chronic atrioventricular block (CAVB) dog model may have a focal origin or are due to re-entry. Also it was found that heterogeneities might play an important role. In the current study we have used computational model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 45 publications
3
40
0
Order By: Relevance
“…In addition, cellular coupling has important roles in modulating EAD generations at tissue level (Pueyo et al, 2011). Although electrotonic coupling can smooth the chaotic EAD behavior (Weiss et al, 2010), regional EADs can propagate into the heterogeneous substrates, resulting in reentry and TdP patterns (Dutta et al, 2016;Vandersickel et al, 2016).…”
Section: From Eads To Clinical Tdp Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, cellular coupling has important roles in modulating EAD generations at tissue level (Pueyo et al, 2011). Although electrotonic coupling can smooth the chaotic EAD behavior (Weiss et al, 2010), regional EADs can propagate into the heterogeneous substrates, resulting in reentry and TdP patterns (Dutta et al, 2016;Vandersickel et al, 2016).…”
Section: From Eads To Clinical Tdp Riskmentioning
confidence: 99%
“…One effective approach to include the tissue effects in TdP risk predictions is whole ventricle simulations (Sato et al, 2009;Moreno et al, 2011;Trayanova, 2011;Dutta et al, 2016;Vandersickel et al, 2016;Martinez-Navarro et al, 2019), however they are computationally much more expensive than the current cell model population which has already shown strong performance. In this study we did not aim to equate EADs and TdP, but rather to use EADs as a pro-arrhythmic risk marker that is mechanistically linked to TdP.…”
Section: From Eads To Clinical Tdp Riskmentioning
confidence: 99%
“…Little is known about the effects of the other drugs simulated here, nebivolol and vardenafil, on fibroblast ion channels. As described previously, proarrhythmic phenomena causing Torsades de pointes (TdP) may be due to action potential heterogeneity in different parts of myocardium, which requires simulations using 2D and 3D special resolutions with different scales (Vandersickel et al 2016). To validate such computational simulations will require experimental samples by which a composition of fibroblasts and cardiomyocytes can be varied.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there is considerable debate regarding the mechanism of perpetuation of TdP beyond the initiating beat. A recent report provides good review of this subject . In a study using 2D and 3D simulation, it was shown that ECG with the typical TdP morphology can be caused by both multiple competing foci and reentrant activity depending on the degree of repolarization heterogeneity .…”
Section: A Paradigm Of Tdp From Ion Channels To Ecgmentioning
confidence: 99%
“…16 In a study using 2D and 3D simulation, it was shown that ECG with the typical TdP morphology can be caused by both multiple competing foci and reentrant activity depending on the degree of repolarization heterogeneity. 16 Large homogeneity can produce ectopic TdP, while small heterogeneity will produce reentry-type TdP. However, the significance of the degree of homogeneity was not shown in other studies.…”
Section: F I G U R Ementioning
confidence: 99%